Stakeholders Involvement In The Development Of Munggu Tourism Village As A Sustainable Tourism Attraction - Kartimin, I Wayan; Arini, Ni Nyoman; Aditya, I Wayan Putra (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2023)
Munggu Tourism Village is one of the villages developed as a community-based tourism village or known as Community Based Tourism (CBT), which is a tourism activity that involves the participation of local communities in the management and development of tourism villages. This study analyzes the role of stakeholders in the development of Munggu Tourism Village and the steps taken in preparing the right strategies and programs for maintaining the sustainability of tourist attractions in Munggu Badung Tourism Village. This study aims to determine the role of stakeholders in the development of Munggu Tourism Village as a sustainable tourist attraction. The approach in this study uses a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The results of this study show that the involvement of stakeholders in the planning and development of Munggu Tourism Village is the main thing to realize sustainable tourism both in the economic, socio-cultural and natural / environmental fields.